A graph-based algorithm for NVM address decoders testing - Scaramuzza, Pierre; Kern, Thomas; Coppetta, Matteo; Grossi, Alessandro; Ullmann, Rudolf (Proceedings - International Test Conference, 2024)
Test coverage and test cost are of primary importance in the production process of microcontrollers for automotive applications. Non-volatile memories play a major role in this respect, and a lot of effort was spent in the past to define strategies for reaching zero-defects targets. This paper introduces a solution for screening defective memory address decoders, with a special focus on RRAM modules architectures. The strength of the proposed approach relies on the definition of a decoder graph model and on an optimal algorithm to traverse it. The presented software-based test, executed on high volumes of several microcontrollers families, decreases field application returns and ensures a consistent test time reduction with respect to the previous implementation.